PENGARUH LAMA MARINASI DENGAN AIR KELAPA TERFERMENTASI TERHADAP KOMPOSISI KIMIA DAGING BROILER - Dinara Saputri; Dian Septinova; Veronica Wanniatie; RR Riyanti (Jurnal Riset dan Inovasi Peternakan (Journal of Research and Innovation of Animals), 2022)
This study aimed to find out the effect of marination period with fermented coconut water on the chemical composition of broiler meat. This research was conducted in July 2020 at the Livestock Production Laboratory, Faculty of Agriculture and Integrated Chemistry Laboratory, Faculty of Mathematics and Natural Sciences, Lampung University. The research materials used were 9 pieces of broiler chest meat. The study used a Complete Randomized Design with 3 treatments and 3 repeatation. Treatment in this study was the length of marinade in fermented coconut water with control/without marinade (M0), 40 minutes (M1), and 80 minutes (M2). The observed changes are water content, protein content, and fat content. The data obtained was analyzed with Analysis of Variance (ANOVA) at a significant level of 5% and if there is a significant difference, it was continued with the Least Significant Difference (LSD) test. The results of this study showed that the long treatment of marination did not affect water content, protein levels, and fat content and the length of marination using fermented coconut water for 40 minutes was the best marination length compared to the length of marination by using fermented coconut water for 80 minutes. Keywords: Broiler meat, Chemical composition, Fermented coconut water, Marinated